Making transnational feminism : rural women, NGO activists, and northern donors in Brazil - Thayer, Millie. (Perspectives on gender (New York, N.Y.), 2010)
"Making Transnational Feminism takes the "ant's eye view" of global social movement relationships from the ground. Using ethnography, Thayer takes us inside transnational feminist alliances, viewing them from the local perspective of two women's movements in Northeast Brazil - one in the remote semi-arid interior and the other in Brazil's fourth largest city, Recife. She finds rural women and NGO feminists appropriating and translating global gender discourses, negotiating with each other over political resources, and strategizing to defend their autonomy from distant donors." "In the process, she argues, the Brazilian organizations help to constitute a transnational feminist political space-a "counterpublic," in which movements debate strategies, articulate new identities, and work to develop alternative social practices. Feminist alliances in this space are characterized by a precarious balance between solidarity and self-interest, collaboration and contention. At the turn of the twentieth century, as markets extended their reach into new regions and social sectors, they also threatened to reshape feminist relationships, undermining the very values on which they were founded. and pushing them toward competitive and instrumental behavior. Thayer shows us how feminist movements in Northeast Brazil struggled to sustain their alliances and to defend their endangered counterpublic against the long hand of the "social movement market.""--Jacket.